URBANIZATION AND SOCIAL CHANGE IN THE POST-PANDEMIC CITY: A CRITICAL INTEGRATIVE REVIEW OF INEQUALITY, COHESION, AND GOVERNANCE (2020–2025) - Endang Setianingsih Susilorini (EDUCATIONE, 2026)
Urbanization is widely framed as a pathway to modernization and improved living standards, yet its social consequences remain theoretically fragmented and empirically contested across contemporary social science scholarship. This study aims to synthesize how recent urbanization processes reshape social structures, cultural norms, and patterns of interaction, while identifying the mechanisms that mediate uneven social outcomes. Using a qualitative critical integrative literature review, the study systematically analyzes peer-reviewed journal articles published between 2020 and 2025, selected from reputable academic databases and coded through a document analysis matrix. The data were examined using thematic and critical content analysis to compare dominant paradigms, underexplored perspectives, and cross-contextual patterns. Findings indicate that urbanization produces non-linear and context-dependent social change. Across settings, urban growth is consistently associated with intensified social stratification, residential and mobility-based segregation, and weakened community cohesion, alongside the emergence of flexible, network-based forms of sociality. Cultural change is characterized less by convergence than by cultural hybridity and contestation as local norms interact with global urban lifestyles. Crucially, governance arrangements and urban infrastructures (housing, transportation, public services) operate as mediating variables that either amplify exclusion or enable inclusion. Post-pandemic dynamics further highlight digital urbanism as a new axis of inequality through persistent digital divides. The study concludes that urbanization should be understood as a socially embedded process whose outcomes depend on institutional capacity and socio-spatial justice. Future research should employ mixed-method and longitudinal designs, expand comparative cases across governance regimes, and treat digital infrastructures as core analytical variables.